PENGEMBANGAN PENDIDIKAN BERBASIS ALAM DAN PEMBERDAYAAN MASYARAKAT LOKAL DI SEKOLAH ALAM TUK SIRAH WINDUAJI KABUPATEN BREBES - Tobirin Tobirin (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
Penjalin, Tuk Sirah reservoirs, and other tourist attractions have encouraging prospects. It is proven by its potential in village economic development, environmental awareness and harmonious and active community in developing villages. However, the process of developing nature-based tourism villages does not yet have adequate best practices to be developed. Therefore, assistance activities are needed in community service activities in Winduaji Village, Paguyangan District, Brebes Regency. The purpose of this Community Service is to assist and ensure the process of developing tourist villages, in terms of concepts, problems, and methods of solving problems directionally. The method of this activity is through mentoring and empowering the community in a participatory bottom-up manner with the active involvement of the local community. This effort is to focus on the development of nature schools and the development of Small Micro and Medium Effort in the local community. It is hoped that Tuk Sirah will become a village tourist destination based on ecological protection. In its implementation, the Nature school is oriented towards collaboration and integration of tourism development by potential through education with curriculum development in the process of raising livestock, fisheries, handicrafts, protecting forest plants, and equestrian sports. In this case, the development of nature schools continues with various forms of training, especially with the development of a nature school curriculum that synergizes with the management of Tuk Sirah nature tourism.